Principal Strategic Management in Improving Teacher Performance at SMKN 6 Garut - R. Supyan Sauri; Khaerul Anwar; Inayah; Siti Halimah (al-Afkar, Journal For Islamic Studies, 2023)
The background of this research is to explain the Principal's Strategic Management in improving teacher performance at SMKN 6 Garut, mentioning the constraints of the Principal's Strategic Management in improving teacher performance at SMKN 6 Garut, describing how to overcome the constraints of the Principal's Strategic Management in improving teacher performance at SMKN 6 Garut. The literature review used to analyze the results of this research is strategic management and leadership of the principal and teacher performance and the principal's strategy in improving teacher performance. The method used in this study is descriptive-analysis using a qualitative approach, data collection techniques with the stages of observation, interviews and documentation. The research procedures are planning, data collection, describing, analyzing and concluding. The results of the study, Strategic Management of school principals in improving teacher performance at SMKN 6 Garut by increasing discipline, providing motivation, being role models for teachers and education staff and supervising. Constraints that occur in the Strategic Management of school principals in improving teacher performance at SMKN 6 Garut, some teachers are late to school, leave earlier than the specified time in ending the school teaching and learning process, are not motivated to improve performance, do not respond to exemplary leadership and supervision in SMKN 6 Garut is held only once a year, lacks school infrastructure, supervisors don't play a role in coaching.